2013
DOI: 10.1002/jbm.b.32949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bleaching agents and soft drink on titanium surface topography

Abstract: The effects of carbamide peroxide, hydrogen peroxide and cola soft drink on the topographic modifications of commercially-pure titanium (CP-Ti) and Ti-6Al-4V were investigated. Ti discs were divided into 18 groups (n = 4) based on the solution treatment and Ti type. Specimens were immersed in 3 mL of each solution for 4 h per day (for the remaining 20 h, discs were left dry or immersed in artificial saliva) for 15 days. For control, specimens were immersed in only artificial saliva. Ti surfaces were examined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…SEM images did not show great changes on the Ti-6Al-4V surfaces. Faverani et al [46] showed that only substantial deterioration can be evidenced on the Ti-6Al-4V alloy surface. Yet, changes in the microstructure of the Ti-6Al-4V alloy in combination with dextrose and LPS were probably due to the impregnation of the substrates used herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM images did not show great changes on the Ti-6Al-4V surfaces. Faverani et al [46] showed that only substantial deterioration can be evidenced on the Ti-6Al-4V alloy surface. Yet, changes in the microstructure of the Ti-6Al-4V alloy in combination with dextrose and LPS were probably due to the impregnation of the substrates used herein.…”
Section: Discussionmentioning
confidence: 99%
“…Each specimen was individually placed in the center of the equipment, with the measuring tip of the profilometer on the specimen surface. Three measurements were performed at different areas on each disc (0.25 mm cut-off at a speed of 0.05 mm/s), and the mean value was calculated [46].…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, most studies use fluorides diluted in Fusayama's artificial saliva solutions at pH 5, to simulate the oral environment in terms of corrosion behavior. Therapeutic bleaching agents based on carbamide (urea) or hydrogen peroxide has also been shown to affect the corrosion resistance of titanium . In the present study, 35% hydrogen peroxide at pH 7 was applied onto the implant system surface.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed changes of titanium surfaces in 0.1‐10% hydrogen peroxide. In the study performed by Faverani et al, titanium and Ti6Al4V surfaces were evaluated by SEM after immersion in solutions based on cola soft drink or hydrogen peroxide diluted in artificial saliva. Those results revealed significant changes on the titanium surface that can affect the long‐term success of the implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation